Effect Of Gentamicin And Neomycin+Bacitracin On Deoxyribonuclease Activity I On The Quality Of Human DNA Of Salivary Origin - Siti Chairani; Zulham Zulham (Journal Of Social Science (JoSS), 2023)
Deoxyribonucleic acid (DNA) can be found in saliva and various other sources. Saliva contains epithelial cells and leukocytes that are released into the oral cavity. Cells in saliva are potential sources of DNA for diagnostic purposes. DNA in saliva can be degraded due to the activity of deoxyribonuclease (DNase), an enzyme that catalyzes the hydrolysis of DNA. DNase I is expressed in exocrine cells while DNase II is expressed in macrophages. Inhibition of DNase activity will preserve DNA. Besides being able to kill bacteria, aminoglycosides (i.e. gentamicin and neomycin) can inhibit DNase. Saliva was collected from 8 subjects. Furthermore, saliva samples from each subject were divided into 4 groups, namely negative control (K1), positive control (K2), gentamicin (K3), and neomycin + bacitracin (K4). DNA was extracted from saliva using the spin column method. DNA from groups K3 and K4 were added to 1 mg/mL gentamicin and 20 mM neomycin + bacitracin, respectively, before adding 2.5 g/mL DNase I (DNA degradation assay). The quality of human genomic DNA from saliva was determined by the presence of the NOTCH2 gene amplicons (~704 bp). DNA was separated by 1% agarose gel electrophoresis and recorded using the gel documentation system. The DNA extracted from saliva using the spin column method had an average concentration of 26.49 + 30.70 ng/mL and an average purity of 1.819 + 0.122. The administration of distilled water as a negative control in the DNA degradation assay showed that no DNA was digested.